2023
DOI: 10.1007/s11357-023-00826-1
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation clock DNAmFitAge shows regular exercise is associated with slower aging and systemic adaptation

Abstract: DNAmPhenoAge, DNAmGrimAge, and the newly developed DNAmFitAge are DNA methylation (DNAm)-based biomarkers that reflect the individual aging process. Here, we examine the relationship between physical fitness and DNAm-based biomarkers in adults aged 33–88 with a wide range of physical fitness (including athletes with long-term training history). Higher levels of VO2max (ρ = 0.2, p = 6.4E − 4, r = 0.19, p = 1.2E − 3), Jumpmax (p = 0.11, p = 5.5E − 2, r = 0.13, p = 2.8E − 2), Gripmax (ρ = 0.17, p = 3.5E − 3, r = … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 23 publications
2
13
1
Order By: Relevance
“…Previous research has demonstrated the influence of acute and regular exercise on global and gene-specific promoter methylation, primarily in peripheral blood and skeletal muscle 5,6 . Recent findings, including those of our study, also indicate a negative relationship between physical fitness (including activity levels and CRF) and epigenetic aging based on age-related changes in DNA methylation levels at CpG sites [7][8][9][10] . These lines of evidence suggest that exercise exerts a rejuvenating effect on epigenetic aging and has a favorable effect on the aging process.…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…Previous research has demonstrated the influence of acute and regular exercise on global and gene-specific promoter methylation, primarily in peripheral blood and skeletal muscle 5,6 . Recent findings, including those of our study, also indicate a negative relationship between physical fitness (including activity levels and CRF) and epigenetic aging based on age-related changes in DNA methylation levels at CpG sites [7][8][9][10] . These lines of evidence suggest that exercise exerts a rejuvenating effect on epigenetic aging and has a favorable effect on the aging process.…”
Section: Introductionsupporting
confidence: 74%
“…This would be consistent with our recent study where we found that standard blood test-based age acceleration largely decreased in male athletes compared to the healthy male controls but did not significantly decrease in female athletes compared to healthy female controls 38 . Other previous study has shown that the age acceleration in the high-fit group was significantly lower than in the medium-to low-fit group for both men and women, but the difference was slightly lower for women 8 . Our previous study also found a significant negative relationship between CRF and age acceleration, but this study included only men 9 .…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Briefly, bisulfite conversion of genomic DNA was performed using the EZ DNA Methylation Kit (Zymo Research, Irvine, CA, USA), followed by hybridization using the Infinium MethylationEPIC BeadChip Kit (Illumina Inc., San Diego, CA, USA). Sample- and probe-based quality checks were performed using the minfi, meffil, and ewastools R packages (14). In this study, all 144 DNA samples met the criteria set by Illumina, and no samples were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Accumulating evidence suggests that the epigenetic clock is associated with lifestyle factors, such as body composition (11), physical activity (12,13) and physical fitness levels (14,15), smoking (16), and alcohol intake (16), and can be delayed or reversed by pharmacological and lifestyle interventions (17)(18)(19)(20). It has also been suggested that healthy dietary patterns, diets rich in fruits and vegetables, and mediterranean diets may delay the epigenetic clocks (21)(22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%